FTR83, a Member of the Large Fish-Specific finTRIM Family, Triggers IFN Pathway and Counters Viral Infection - Langevin, Christelle; Aleksejeva, Elina; Houel, Armel; Briolat, Valérie; Torhy, Corinne; Lunazzi, Aurélie; Levraud, Jean-Pierre; Boudinot, Pierre (Frontiers in Immunology, 2017)
Tripartite motif (TRIM) proteins are involved in various cellular functions, and constitute key factors of the antiviral innate immune response. TRIM proteins can bind viral particles directly, sending them to degradation by the proteasome, or ubiquitinate signaling molecules leading to up-regulation of innate immunity. TRIM proteins are present in across metazoans, but are particularly numerous in vertebrates where genes comprising a B30.2 domain have been often duplicated. In fish, a TRIM subset named finTRIM is highly diversified, with large gene numbers and clear signatures of positive selection in the B30.2 domain suggesting they may be involved in antiviral mechanisms. finTRIM provide a beautiful model to investigate the primordial implication of B30.2 TRIM subsets in the arsenal of vertebrate antiviral defenses. We show here that ftr83, a zebrafish fintrim gene mainly expressed in the gills, skin and pharynx, encodes a protein affording a potent antiviral activity. In vitro, overexpression of FTR83, but not of its close relative FTR82, induced IFN and IFN-stimulated gene expression, and afforded protection against different enveloped and non-enveloped RNA viruses. The kinetics of IFN induction paralleled the development of the antiviral activity, which was abolished by a dominant negative IRF3 mutant. In the context of a viral infection, FTR83 potentiated the IFN response. Expression of chimeric proteins in which the B30.2 domain of FTR83 and the non-protective FTR82 had been exchanged, showed that IFN up-regulation and antiviral activity requires both the RBCC domain (supporting E3 ubiquitin ligase) and the B30.2 domain of FTR83. Finally, loss of function experiments in zebrafish embryos confirms that ftr83 mediates antiviral activity in vivo. Our results show that a member of the largest TRIM subset observed in fish up-regulates type I IFN response and afford protection against viral infections, supporting that TRIM are key antiviral factors across vertebrates.